2022
DOI: 10.1039/d2an01317g
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput and directed microparticle manipulation in complex-shaped maze chambers based on travelling surface acoustic waves

Abstract: High-throughput automated manipulation of microparticles in complex-shaped environments has been demonstrated with great potential in the fields of pharmaceutical microfluidics. Generally, high efficient actuation method for functional microparticles’ manipulation in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…The transport of cells in specific pathways is of great value in engineering and clinical research, such as directed tissue engineering, 156,157 organic macromolecule assembly, 158 and targeted drug delivery. 92 In 2003, Wixforth et al 159 reported for the first time that TSAWs generated by a set of cross-finger transducers on a piezoelectric substrate drove droplets along a pre-determined trajectory. As shown in Fig.…”
Section: Tsaw-based Transportmentioning
confidence: 99%
“…The transport of cells in specific pathways is of great value in engineering and clinical research, such as directed tissue engineering, 156,157 organic macromolecule assembly, 158 and targeted drug delivery. 92 In 2003, Wixforth et al 159 reported for the first time that TSAWs generated by a set of cross-finger transducers on a piezoelectric substrate drove droplets along a pre-determined trajectory. As shown in Fig.…”
Section: Tsaw-based Transportmentioning
confidence: 99%